Comparison of Intraocular Pressure (IOP) Value Before and After Vitrectomy in Diabetic Retinopatic Patients - Arnila Novitasari Saubig; Fifin Luthfia Rahmi; Hesti Triwahyu Hutami (Jurnal Kedokteran Diponegoro, 2021)
Background: Diabetic retinopathy is one of the second highest complications of microangiopathy in Indonesia due to diabetes mellitus in the form of damage to retina of the eye and can cause blindness in adults. The management of diabetic retinopathy is done by operative measure, one of which vitrectomy. However, this procedure can lead to an increase in the value of intraocular pressure after surgery. In this study, analysis of differences in intraocular pressure values before and after vitrectomy was carried out in patients with diabetic retinopathy.